PERANAN DAN PENGEMBANGAN SISTEM INFORMASI MENAJEMEN DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Tambunan, Sagdiyah Fitri Andani; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Transpublika Publisher, 2022)
Management information system (MIS) is an instrument for processing, analyzing, and displaying data so that it can be used for decision making. To assist business processes, this system is a very essential tool. Management information systems (MIS) support operations, management, analysis, and general organizational decision-making processes. This article aims to find out how the functions and progress of management information systems in improving the quality of education. The results show that the SIM database and management are connected for analysis, planning, monitoring, and decision making. 1) Providing the necessary information or data for the benefit of student data, student grades, teachers, and the goals achieved by school leaders is one of SIM's roles in improving the quality of education. 2) As a decision-making room. 3) Management information systems can increase the availability of information that is disclosed in a timely and accurate manner without intermediary existing information systems 4) Become a medium for promoting school presentations 5) Provide provisions for students to follow developments both from an academic and non-academic perspective 6) Decision makers SIM development training can easily find information as material in the decision-making process.